Role for intrarenal mechanisms in the impaired salt excretion of experimental nephrotic syndrome. - Ichikawa, I (1983)
A unilateral model of puromycin aminonucleoside (PAN)-induced albuminuria was produced in Munich-Wistar rats to examine the mechanisms responsible for renal salt retention. 2 wk after selective perfusion of left kidneys with PAN (n = 8 rats) or isotonic saline (control, n = 7 rats), increases in albumin excretion and decreases in sodium excretion were demonstrated in PAN-perfused but not in nonperfused kidneys of PAN-treated rats although systemic plasma protein concentration remained at control level. Total kidney glomerular filtration rate (GFR) and superficial single nephron (SN) GFR were also reduced selectively in PAN-perfused kidneys, on average by approximately 30%, due primarily to a marked decline in the glomerular capillary ultrafiltration coefficient (Kf), which was also confined to PAN-perfused kidneys. Values for absolute proximal reabsorption (APR) were also selectively depressed in PAN-perfused kidneys, in keeping with a similarly selective decline in peritubular capillary oncotic pressure measured in these kidneys, the latter also a consequence of the fall in Kf. In a separate group of seven PAN-treated rats, however, no differences were detected between PAN-perfused and nonperfused kidneys in the absolute amount of sodium reaching the early (0.77 +/- 0.09 neq/min vs. 0.74 +/- 0.08, P greater than 0.40) and late portions of superficial distal tubules (0.31 +/- 0.02) neq/min vs. 0.32 +/- 0.05, P greater than 0.50), despite the lesser filtered load of sodium in PAN-perfused kidneys. Suppressed sodium reabsorption in both proximal convoluted tubules and short loops of Henle of PAN-perfused kidneys contributed to this equalization of sodium delivery rates to the late distal tubule, as did comparable reabsorption along distal convolutions. In two additional groups of PAN-treated rats, infusion of saralasin (0.3 mg/kg per h, i.v.) led to substantial increases in total kidney GFR and SNGFR in PAN-perfused but not in nonperfused kidneys. Despite these increases in total and SNGFR, urinary sodium excretion by PAN-perfused kidneys remained at a level far below that for nonperfused kidneys, again indicating that the antinatriuresis characterizing the PAN-perfused kidney is due to alterations in sodium handling by the tubules rather than changes in GFR. These results therefore indicate (a) that reductions in Kf and depressed sodium reabsorption by proximal tubules and Henle's loop segments in this model are brought about by intrarenal rather than circulating or systemic factors, and (b) assuming that superficial nephrons are representative of the entire nephron population, renal salt retention in this model is due primarily to intrarenal factor(s) acting beyond the distal convolution.